Shawnasi Kurdistan, this is the valley and the Javanese, so this is the Arabic language and the valley is Arabic and Mosafiriyakan. - Hamarshid, Mariwan Abdul Abdullah (Sulaimani Journal for Humanities, 2025)
Research on Kurdish history in Islamic times is vague because Islamic sources describe Kurdish history secondarily within the framework of the caliphate. The history of the Rawadi family falls within this framework. There is little information about it and it is vague. However, it is important to clarify the history of this tribe because it is one of the most important Kurdish tribes. In this study we want to investigate the origin of the Rawadi tribe, which was one of the famous Kurdish tribes and established a strong empire and historical sources attribute the origin of the greatest leader of the Islamic and Kurdish world In this study, we want to investigate the origin of the Rawadis according to historical sources and present the opinions of some historians in this regard.